PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU DI MTS. AR-RAHMAH KOTA TASIKMALAYA - Rowi Karim, Aja (HASBUNA : Jurnal Pendidikan Islam, 2025)
Improved education quality is strongly influenced by the teaching learning process. If this process is corrected, then the quality of the graduates will improve. School Management and the principal teaching approach greatly determine the quality of learning. The principal should be able to communicate the vision to students, parents, teachers, and administrators. Teacher competence is important to carry out tasks in the field of learning. The low quality of education is due to the low performance of teachers, which is influenced by various aspects of competence such as personality, pedagogic, social, and professional. The main cause of low quality teachers is the role of principal. The principal serves to improve the pedagogic competence of teachers, which is essential for the educational process. A Headmaster should be able to guide and motivate, as well as maintain good communication and supervision in school. Researchers are interested in exploring the role of principal in improving the pedagogic competence of teachers at MTs. Ar-Rahmah Tasikmalaya City. This research uses a qualitative descriptive research approach. Qualitative research is research that produces description data, both speech and writing and behavior that can be taken from the people or subject itself. So, qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behaviors. The Headmaster has an important role in improving the pedagogic competence of teachers through functions as educators, managers, administrators, supervisors, leaders, innovators, and motivators. The principal should create a good learning climate, support teachers in professional activities, and motivate to improve performance. Some strategies are done to improve pedagogic competencies, including conducting workshops, tattoos, motivations for scientific writing, awarding, supervision, and school meetings. From research on MTs. Ar-Rahmah Tasikmalaya City, it was concluded that the principal as a leader should implement strategies to motivate teachers in improving their pedagogic competencies.